Las plataformas virtuales para la enseñanza en el idioma inglés en la Unidad Educativa “16 De Mayo” en el primer año de bachillerato - Lindao Jiménez, Jennifer Jacqueline (2019)
The present research work is a case study, the theme is: "THE VIRTUAL PLATFORMS FOR THE TEACHING OF THE ENGLISH LANGUAGE OF THE EDUCATIONAL UNIT" MAY 16 "IN THE FIRST YEAR OF BACHILLERATO, which constitutes a new didactic mechanism of knowledge and transfer for language teaching-learning, in which virtual applications such as: gmail, internet, wiki, facebook, email, youtube and blog are implemented, which help improve teaching to achieve a better level of learning in students, The platforms are not only tools for work, study and archiving but they are also sociological phenomena that are increasing among countries and cultures. The Educational Unit "May 16" constitutes the Unit of analysis of this pedagogical case, the demographic delimiter determined first year high school students “A” and “B”, with a total of 80 students, the surveys were applied m By sampling technique, 40 from a universe of 80 students. Another demographic delimiter adapted to the teachers of the Educational Unit "May 16" with a total of 6 teachers; The surveys are applied through the sampling technique, the methodology used for the deductive method because it goes from the generals that is the Educational Unit “May 16” to the particular students of the first year of high school